Efficacy and safety of low-concentration, bisulphite-containing, intracameral epinephrine and topical atropine treatments for the prevention of intraoperative floppy iris syndrome - TOKER, AYŞE EBRU (TAYLOR & FRANCIS LTD, 2018)
Purpose: The aim of this study was to evaluate the efficacy and safety of topical atropine and topical atropine combined with intracameral low-concentration, bisulphite-containing epinephrine treatment for the prophylaxis of intraoperative floppy iris syndrome.Materials and methods: Seventy-two eyes of 55 male patients who were treated with alpha-adrenergic antagonist medications for benign prostatic hyperplasia were included in this study. Standard premedication with topical cyclopentolate, phenylephrine, tropicamide and ketorolac was applied to all of the patients. In 22 cases no further prophylactic method was used (Group-NP), while in 29 cases topical atropine drops was instilled 12h and 30min before surgery (Group-A) and in 21 cases 1:16000 epinephrine was injected to the anterior chamber at the beginning of surgery (Group-EA) in addition to topical atropine prophylaxis.Results: In Group-NP, 62.8% of the cases developed IFIS, while development of IFIS was significantly lower in Group-A (17.2%, p=0.0004) and Group-EA (9.5%, p<0.0001). Posterior capsule rupture was observed in two cases (9.1%) in Group-NP, in one case (3.4%) in Group-A and was not observed in Group-EA. There was no statistically significant difference between the groups for the development of surgical complications. We did not observe any adverse events or significant endothelial cell loss (p=0.462).Conclusions: Our results indicate that preoperative use of topical atropine reduces the incidence of IFIS. Use of low-concentration, bisulphite-containing epinephrine is more effective in the prevention of IFIS and does not cause preservative related endothelial damage. This prophylaxis may be preferred when preservative free epinephrine is not available.
Keywords: Intraoperative floppy iris syndrome; epinephrine; atropine; IFIS prophylaxis; cataract surgery; CATARACT-SURGERY; CORNEAL ENDOTHELIUM; TAMSULOSIN; ANTAGONISTS; ASSOCIATION; PROPHYLAXIS; MANAGEMENT; IFIS